2020
DOI: 10.1039/d0nr06719a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in optical and optoelectronic data storage based on luminescent nanomaterials

Abstract: The recent achievements in luminescent nanomaterials used in optical and optoelectronic data storage have been reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 181 publications
0
45
0
Order By: Relevance
“…LSC is composed of organic salts that are designed to absorb specific UV and/or IR light and to transform it into another wavelength out of visible range. This new wavelength is then guided to the edge of the window, being converted into electricity by thin SPV cell strips [ 116 ].…”
Section: Glass In Smart Materials and Opto-electronic Devicesmentioning
confidence: 99%
“…LSC is composed of organic salts that are designed to absorb specific UV and/or IR light and to transform it into another wavelength out of visible range. This new wavelength is then guided to the edge of the window, being converted into electricity by thin SPV cell strips [ 116 ].…”
Section: Glass In Smart Materials and Opto-electronic Devicesmentioning
confidence: 99%
“…[ 21 ] Common strategies developed to store information strongly rely on the preparation of luminescent inks based on lanthanide‐doped nanomaterials. [ 22 , 23 , 24 , 25 , 26 ] Information patterns are generally prepared by printing luminescent inks on external supporters. [ 22 , 27 , 28 ] However, due to the weak mechanical strength, low toughness, fragility, or poor integrity of the inks, [ 29 , 30 ] the stored information may easily be damaged under deformations and thus the systems could not be applied for information storage in complex scenarios, such as flexible devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MoS 2 quantum dots (MoS 2 -QDs) exhibit a high quantum yield and a broadening of excitonic absorption owing to the enhanced spin–valley coupling and strong exciton binding energy [ 12 ]. Furthermore, recent studies about semiconductor QDs (MX 2 -based QDs) successfully suggested their potential in memory devices and neuromorphic computing because of the tunable electrical/optical characteristics of the QDs [ 13 ]. On the other hand, research on metallic-MoS 2 QDs ( m -MoS 2 -QDs), which possess interesting characteristics, such as photophysical properties, is rarely reported because of the metastable nature of the metallic phase compared with that of semiconducting MoS 2 -QDs (e.g., 2H-MoS 2 -QDs).…”
Section: Introductionmentioning
confidence: 99%